Implementing Nature-based Solutions: Learning from Benchakitti Forest Park in Bangkok - Likitswat, Fa; Sung, Chatchanin (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Given the limited number of case studies reflecting Nature-based Solutions (NbS) implemented in the Global South, existing cases of NbS within the city of Bangkok offer valuable lessons. This article aims to document and discuss the design process involved in implementing the NbS concept for Benchakitti Forest Park in Bangkok. The methodology involves a narrative literature review, qualitative content analysis, and interdisciplinary discussion. The article is complemented by insights from the landscape architect responsible for the park’s design and inspection during the construction process. The results are presented in three parts: optimizing the benefits of NbS, barriers to NbS, and the implementation of the design for Benchakitti Forest Park in Bangkok. The discussion centers on exploring opportunities and challenges in implementing the NbS concept, particularly in the context of a tropical monsoon climate. By deepening the understanding and contextualizing NbS, Benchakitti Forest Park is proposed as a valuable case study for learning landscape architectural design concepts and strategies related to NbS, offering efficient local construction methods, and adhering to specified time frames and budgets. At the early stage after opening to the public in 2022, there should be scientific proof of the park’s performance reflected in ecosystem services and disservices. Our study emphasizes the need for a long-term site monitoring program, landscape management framework, and guidelines to manage the urban wild space which should be integrated with educational programs and multi-stakeholder visioning for NbS.